Biomass-derived nanocellulose aerogel enable highly efficient immobilization of laccase for the degradation of organic pollutants. (July 2022) - Wu, Dingsheng; Lv, Pengfei; Feng, Quan; Jiang, Yu; Yang, Hanrui; Alfred, Mensah; Wei, Qufu
Graphical abstract: Highlights: PHEMA-BC aerogel were prepared through biosynthesis and ATRP modification. The amount of laccase immobilized on aerogel was 130.4 mg/g, showing high activity. The designed biocatalyst platform had excellent storage stability and reusability. Degradation rates of reactive red X-3B and 2, 4-dichlorophenol were 94.5% and 85.2%. Immobilized laccase remained more than 76% relative activity after 5th reusability. Abstract: Laccase is a promising biocatalyst for pollutant degradation and water purification. However, laccase can only improve the stability of enzyme activity and achieve its significant catalytic effect after effective immobilization. Herein, we report a general strategy to integrate nanocellulose aerogel and laccase for high-efficiency degradation of organic pollutants. Biomass-derived functional bacterial cellulose (BC) aerogel with a nanonetwork structure and high porosity was prepared by biosynthesis, solvent replacement, and atom transfer radical polymerization (ATRP) procedures. Subsequently, a biocatalyst platform was fabricated by "coupling" ATRP-modified BC aerogel with abundant active sites with laccase through ion coordination. The results demonstrated the biocatalyst platform not only has good biological affinity, but also has high enzyme load and structural stability. Meanwhile, the degradation rates of reactive red X-3B and 2, 4-dichlorophenol reached 94.5% and 85.2% within 4 h, respectively. The strategy disclosed herein could provide a practical method for the degradation of organic pollutants.